Constitutive modeling for time- and temperature-dependent behavior of composites. (1st March 2020) - Rique, Orzuri; Liu, Xin; Yu, Wenbin; Pipes, R. Byron
Abstract: Structural integrity, durability, and thermal stability represent critical areas for adequately modeling the behavior of composite materials. Polymeric matrices are prone to have time-dependent behavior very sensitive to changes in temperature that influence the effective properties of the composite. This study extends mechanics of structure genome (MSG) to construct a linear thermoviscoelastic model that allows to homogenize three-dimensional heterogeneous materials made of constituents with time- and temperature-dependent behavior. The formulation models the transient strain energy based on integral formulation for thermorheologically simple materials and treats thermal expansion creep as inherent material behavior. An analytical three-dimensional thermoviscoelastic homogenization solution has been derived for laminates modeled as an equivalent, homogeneous, anisotropic solid. Three-dimensional representative volume element (RVE) analyses and direct numerical simulations using a commercial finite element software have been conducted to verify the accuracy of the MSG homogenization. Unlike MSG, the RVE method exhibits limitations to properly capture the long-term behavior of effective coefficients of thermal expansion (CTEs) when time-dependent constituent CTEs are considered. The analyses of the homogenized properties also reveal that the shift factor of the polymeric matrix drives the temperature dependencies of the effective CTEs and engineering constants of the heterogeneous composite material regardless of the structural scale.